2012
DOI: 10.1002/ibd.21798
|View full text |Cite
|
Sign up to set email alerts
|

Association of peroxisome proliferator-activated receptor gamma polymorphisms with inflammatory bowel disease in a Hungarian cohort

Abstract: In the present study we demonstrated a significant association between PPARγ polymorphisms and the development of CD and UC at single loci level and also in haplotype combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…3 studies recruited healthy blood donors as controls [10], [20], [21]. One study recruited healthy medical staff as controls [11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 studies recruited healthy blood donors as controls [10], [20], [21]. One study recruited healthy medical staff as controls [11].…”
Section: Resultsmentioning
confidence: 99%
“…The association between the PPARγ Pro12Ala polymorphism and UC in the European Caucasian population was investigated in 2 studies with 598 UC cases and 1271 controls [10], [21]. There was no significant association between the Pro12Ala polymorphism and UC in the European Caucasian population (Pro vs Ala: OR = 1.047, 95%CI = 0.858–1.277, P  = 0.651, Bon = 1.000; ProPro vs ProAla: OR = 1.157, 95%CI = 0.917–1.459, P  = 0.219, Bon = 1.000; ProPro vs AlaAla: OR = 0.680, 95%CI = 0.346–1.335, P  = 0.263, Bon = 1.000; ProAla vs AlaAla: OR = 0.586, 95%CI = 0.293–1.173, P  = 0.131, Bon = 0.917; Pro homozygotes vs Ala positives: OR = 1.109, 95%CI = 0.886–1.388, P  = 0.365, Bon = 1.000; Pro positives vs Ala homozygotes: OR = 0.653, 95%CI = 0.334–1.280, P  = 0.215, Bon = 1.000; heterozygotes vs all homozygotes: OR = 0.854, 95%CI = 0.678–1.077, P  = 0.183, Bon = 1.000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15, 16, 17 The PPAR γ agonists inhibit Th17 cell differentiation in lung myeloid dendritic cells and promote Treg cell differentiation in the white adipose tissue of mice. 18, 19, 20, 21 Meanwhile, various pentacyclic triterpenes were reported to activate PPAR γ . 22, 23 These findings suggested that the triterpenes in C. asiatica might restore the Th17/Treg balance through the PPAR γ pathway.…”
mentioning
confidence: 99%
“…PPAR-γ2 is a sub-type of PPAR that is only expressed in adipose tissue (14). The Pro 12 Ala single nucleotide (rs1801282) polymorphism is a C/G mutation that may be associated with the modifications of the risk of a number of diseases (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%